Aspectos jurídicos da inseminação artificial heteróloga - Barros, Eliane Oliveira (2007)
The present article deals with the subject related to the Legal aspects of the heterologue artificial insemination . The objective of the study was to analyze the main problems related to this kind of attended reproduction, among them: the probable users of this technique; to discuss the possibility of attribution of the paternity results of the permission given by the husband to the wife or by one companion to the other so that she submits herself to therapeutical procedure; to consider if the child born through the use of this technique can have access to the identity of the donator; to know if the donator can be considered the father of the child. The study is justified due to the scarce normative treatment given to the subject by the Civil Code. The article used method of qualitative bibliographical research. It had been examined some works of reference that had best dealt with the subject among available ones